Review of modifications of activated carbon for enhancing contaminant uptakes from aqueous solutions - Yin, C.Y.; Aroua, M.K.; Daud, W.M.A.W. (Separation and Purification Technology, 2007)
Due to its versatility and wide range of applications, activated carbon is widely used as contaminant removal media. Recent research have focused on enhancing the effectiveness of activated carbon by modifying their specific properties in order to enable the carbon to develop affinity for certain contaminants. In view of this, a comprehensive list of literatures on chemical, physical and biological modification techniques of activated carbon pertaining to enhancement of contaminant removal from aqueous solutions was compiled and reviewed. Acidic treatment to introduce acidic functional groups onto surface of activated carbon was by far, the most studied technique. It was apparent from the literature survey that the beneficial effects of specific modification techniques on activated carbon adsorption of targeted contaminant species from aqueous solutions were profound, with some studies reported increase of contaminant uptake factors of more than 2. Concurrently, considerable decreases associated with certain contaminant uptakes can also occur depending on the technique used.